Communication in Business Organizations - Niraula, Ganesh Prasad (Academic Voices: A Multidisciplinary Journal, 2013)
Now a day, communication has become central part of management. It has been used by different business houses like sole trading, partnership and joint stock companies in their different managerial and non-managerial activities. Its role is inevitable not only in the business organizations but also in our day to day life. Communication is the transformation of information from one person to another to fulfill common interest. It is the exchange of facts, opinions, ideas suggestions and other information. This paper deals with the relevance and role of communication in business organization. Academic Voices, Vol. 2, No. 1, 2012, Pages 23-27 DOI: http://dx.doi.org/10.3126/av.v2i1.8281